Facultad de Ciencias Administrativas participó en Expo Feria Universitaria en el Campus Gabriel Galarza López - García García, Mariana (2023)
Administrative Sciences, he presented his majors to the Educational Units of the city and province: Communication; Turism and hotelery; Accounting and auditing; Business Administration; Marketing; Software; Entrepreneurship and Social Innovation; Information Technology and Human Talent, each profession offered by the Alma Mater, captured the attention and interest of the young people from the educational establishments who visited the stands, bringing information about the offer from the State University of Bolívar.